Safety and feasibility of endoscopic sinus surgery as an office-based procedure - Abrahamsson, Sebastian; Kolari, Terhi; Numminen, Jura; Irjala, Heikki (Rhinology Online, 2025)
Background: The purpose of this study was to evaluate whether office-based endoscopic sinus surgery (ESS) is as safe as traditional outpatient surgery and whether there are differences in the operation results, patient recovery data, or complication and revision surgery rates.
Methods: The study involved 164 subjects and data was collected retrospectively from Seinäjoki Central Hospital patient records.The office-based group included 92 patients who had undergone ESS under local anaesthesia in an office-based setting between April 2014 and December 2017, and the outpatient group 72 patients who had done so in an outpatient setting between January 2010 and December 2014. Patients were divided into two groups based on presence (wNPs, n=57) or absence (sNPs, n=107) of
nasal polyps.
Results: We found statistically significant differences in intraoperative medication in terms of amounts of drugs administrated. Sick leave was on average 2.1 days longer in the outpatient sNPs group and 2.4 days longer in the outpatient wNPs group than in the respective office groups. There were no statistically significant differences between methods in terms of complications.Revision rates for sNPs were 5.6% and 13.9% for the office and outpatient groups, respectively, and for wNPs 4.8% and 19.4%, respectively.
Conclusion: Office-based ESS with careful patient selection seems safe, effective, and well tolerated by patients. Office-based intervention may lead to shorter sick leave durations and can reduce the overall use of sedative drugs during the operation.